Multiple Criteria Decision Analysis for Off-Patent Pharmaceuticals in Health Care: Bibliometric Analysis and Scoping Review - Ratih Puspita Febrinasari; Erna Kristin; Aiman Hilmi Asaduddin; Meutia Filzan Kamilah; Dinari Febriyanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Multi-Criteria Decision Analysis (MCDA) is a structured approach used for evaluating complex decisions that involve multiple criteria. In the context of healthcare, its use has grown significantly for benefit–risk assessments, formulary decisions, and reimbursement processes. In developing countries, MCDA has been proposed to support evidence-based evaluation of off-patent pharmaceuticals (OPPs), helping improve public health outcomes and access to quality medicines. However, existing reviews remain limited in scope, emphasizing the need for an updated bibliometric overview of MCDA applications in OPPs.Objectives: This study aims to provide a comprehensive bibliometric analysis of MCDA research in healthcare, with a specific focus on OPPs.Methods: Searches were conducted in Scopus, PubMed, and Epistemonikos from January 1985 to October 2023. Eligible studies included full-text English articles utilizing MCDA in OPP procurement. Data were extracted on decision contexts, criteria, methodologies, and stakeholder involvement. Bibliometric analysis was conducted using Scopus Analyzer, VOSviewer, and Microsoft Excel.Results: A total of 2,210 MCDA-related healthcare articles were identified from 1981 to 2023, with a marked increase after 2013. Dominant themes included decision-making, multicriteria analysis, and healthcare. The identification results showed that A.A. Zaidan was the most prolific author. Citation analysis reported 41,882 citations between 2011 and 2023. The scoping review identified seven studies focusing on MCDA for OPPs, highlighting quality as the most prioritized criterion in procurement frameworks.Conclusion: MCDA frameworks offer a comprehensive approach to improve healthcare decision-making and policy development, particularly in evaluating and procuring OPPs, while supporting adaptable implementation across diverse health systems.